Learning by Doing ": Predictive Models in the Teaching and Learning of Statistics (APRENDER HACIENDOâ: MODELOS PREDICTIVOS EN LA ENSEÃANZA Y APRENDIZAJE DE ESTADÃSTICA) - Fernando Zamora Canova**, Carlos Medina Tello***, Javier Alonso Trujillo*, Abraham Alonso Ricardez* (Social Science Learning Education Journal, 2017)
Nursing, one of the bachelor offered by Faculty of Top Studies Iztacala, UNAM, there are special interest on teachers that teaching research methodology, in which the education of the Statistics (basic tool in scientific methodology) uses as far as possible the educational available technology in the faculty, as the Internet and specialized software (SPSS and Excel).Thus, the former strategies are left behind as the resolution of exercises in which the students, using a calculator, realized a great quantity of mathematical necessary calculations to demonstrate a statistical hypothesis, or the consultation of tables of diverse distributions probabilÃsticas with an immense quantity of numbers in that one was looked especially and where the students were ending accidentally to know nothing of the numbers. In this work there appears the form in which the use of predictive models included in the statistical software SPSS, specifically the model Classificatio and regression tres, helps to understand concepts hypothesis testing, value "p" and probability.Results. A nursing student obtained his professional title and demonstrated sufficient knowledge it brings over of basic concepts in Statistics. We concludes that the use of predictive models support the learning of the students.Â Key Words. Nursing, Teaching, Statisitc, forecasting models